Determining the Extent to which the Firm Value Responds to the Characteristics of the Quality of Accounting Profits : An Application in a Sample of Iraqi Contributing Banks for the Period (2015-2020) - Ragab, Ava Sh.; Rasheed, Shiler A. (Mitanni Journal of Humanitarian Sciences, 2023)
The current research focused on testing the relationship and influence between the characteristics of the quality of accounting profits and the value of the establishment of the Iraqi contributing banks, which numbered (16) banks and for a period of (6) years (2015-2020). The secondary data collected from the annual and semi-annual reports of the listed banks used, and the multiple linear regression model relied upon to test the relationship between the quality of accounting profits as an independent variable, which measured by (quality of receivables, estimated receivables, predictive ability, and continuity of profits). In addition, the value of the enterprise as a dependent variable, which measured by (Tobin’s Q, market value to book value). The results showed that there is no significant correlation between the characteristics of the quality of accounting profits and the value of the establishment. As well as the absence of a statistically significant effect relationship between the characteristics of the quality of accounting profits and the value of the establishment. This indicates that investors in the Iraqi environment do not study and evaluate the quality of the profits disclosed in banks, and do not take into account the relative amount of the components of receivables and cash flows, but are concerned with the total sum of the profits disclosed. This indicates that investors in these markets interpret the net profit in a consistent manner, regardless of the accounting policies and tools that used to reach this profit. The research recommends the need to give greater importance to the quality of accounting profits because it is one of the most important tools that help in measuring the quality of accounting profits in light of the spread of wrong accounting practices to maximize the value of the establishment. By increasing the quality of financial reports. Keywords: quality of accounting profits, value of the establishment, receivables.